How Digital Marine Technologies Improve Small-Island Livelihoods: The Roles of Sustainable Practices, Productivity, and Institutional Support - Jani Jani; Rukmuin Wilda Payapo; Ervan Togatorop; Venezia Thalia Metekohy; Arjen Robben Doddy Sahanaya (Pattimura University, 2026)
Small Island Developing States (SIDS) face acute vulnerabilities in marine-dependent livelihoods due to declining fish stocks, environmental degradation, and limited economic diversification. While Digital Marine Technologies (DMTs) have been proposed as tools to enhance productivity and sustainability, the integrated mechanisms linking DMT adoption to livelihood outcomes remain under-explored, particularly the role of institutional support in moderating these effects. Addressing this gap, the present study examines how DMTs contribute to small-island livelihood resilience through economic and environmental pathways. Employing a quantitative cross-sectional survey design, data were collected from 750 respondents comprising small-scale fishers and cooperative managers across representative SIDS communities. The study tested complex relationships using Partial Least Squares Structural Equation Modeling (PLS-SEM), allowing for simultaneous assessment of direct, mediated, and moderated effects within the proposed conceptual framework. The results indicate that DMT adoption exerts a significant positive direct effect on small-island livelihoods. Further, Productivity and Sustainable Practices were confirmed as significant mediators, demonstrating that technological benefits materialize through both enhanced economic performance and improved resource stewardship. Importantly, the positive impact of DMTs on livelihoods is strengthened under conditions of high Institutional Support, highlighting the conditional nature of technology effectiveness in these contexts. The study contributes theoretically by validating an integrated framework in which technological adoption, livelihood gains, and environmental sustainability are mutually reinforced and contingent on governance quality. Practically, the findings underscore that policy interventions in SIDS must go beyond technology provision, prioritizing institutional development, infrastructure investment, and capacity building to ensure equitable and sustainable livelihood improvements.